JILBAB: MENUTUP AURAT PEREMPUAN (Analisis Surat An Nur Ayat 31) - H, Zaenudin (Kopertais Wilayah X Jawa Tengah, 2017)
Abstract Aurat is a member of the body that must be closed and should not be seen by others. Aurat is divided into two categories namely for the adam and for the Eve. For Adam the aurat is the whole limb between center and knee. While the aurat for women is the whole body except the face and both palms. For women to close all limbs is a necessity because it is a command of Islam.Â Along with the provision of closing the aurat of paragraph 31 of the letter an-Nur is a command from Allah SWT in order to cover the head covering the popular language wearing hijab. Jilbab is one of the rides to cover aurat for women. The female head must be sealed in such a way as to be free to be viewed by others who are not mahrom. Problems want to use any model head cover depending on the user's taste as long as it is smart for the wearer and cover the head. Hair that be female mahota should not be wildly perurai regarded by anyone, must also be closed tight so as not to invite slander